Concevoir une formation : réflexion sur une démarche d’aide à l’apprentissage sur le cours de vie - Pierre-Sébastien Fournier (Perspectives Interdisciplinaires sur le Travail et la Santé)
This article proposes reflection on the theoretical models used to understand the occupational training design methods related to the reality of work and reflection on ways to improve the design process from an activity analysis perspective. This reflection allows different training development approaches to be compared. The approach chosen is the conception of action situations on the course of life that proposes establishing learning support. This choice makes it possible to identify the nature of the intervention to be developed and thereby raises questions about the activity analysis process that must be adopted to fulfill this mandate. These questions force us to consider other human activity-related trends that propose different but compatible processes and that identify means of improvement that deserve further exploration.